Congenital and Perinatal Viral Infections: Consequences for the Mother and Fetus - Mariam Al Beloushi; Huda Saleh; Badreldeen Ahmed; Justin C. Konje (Viruses, 2024)
Viruses are the most common congenital infections in humans and an important cause of foetal malformations, neonatal morbidity, and mortality. The effects of these infections, which are transmitted in utero (transplacentally), during childbirth or in the puerperium depend on the timing of the infections. These vary from miscarriages (usually with infections in very early pregnancy), congenital malformations (when the infections occur during organogenesis) and morbidity (with infections occurring late in pregnancy, during childbirth or after delivery). The most common of these viruses are cytomegalovirus, hepatitis, herpes simplex type-2, parvovirus B19, rubella, varicella zoster and zika viruses. There are currently very few efficacious antiviral agents licensed for use in pregnancy. For most of these infections, therefore, prevention is mainly by vaccination (where there is a vaccine). The administration of immunoglobulins to those exposed to the virus to offer passive immunity or appropriate measures to avoid being infected would be options to minimise the infections and their consequences. In this review, we discuss some of the congenital and perinatal infections and their consequences on both the mother and fetus and their management focusing mainly on prevention.